PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN MINUMAN MEREK TEH PUCUK HARUM PADA TOKO DHEA SEMBAKO DI TANAH GROGOT - Islamiah, Farida; Harmayanto, Harmayanto; Jayanti, Riska Dinda (Universitas Gajah Putih, 2023)
This study aims to determine the effect of the marketing mix on purchasing decisions for Teh Pucuk Harum. The type of research used is explanatory research with a quantitative approach. The sampling technique used is incidental sampling with a sample of 60 people. Collecting data using a questionnaire consisting of 31 statements. The data analysis technique used is multiple linear regression analysis. The results showed that the marketing mix consisting of product, price, promotion and place simultaneously and partially had a positive and significant effect on purchasing decisions for Teh Pucuk Harum.